Penguatan Pendidikan Karakter di Wilayah Perbatasan dalam Mempertahankan Identitas Nasional (Studi Kasus SMPN 3 Sajingan Besar Kabupaten Sambas) - Lala, Lala; Zakso, Amrazi; Atmaja, Thomy Sastra; Mashudi, Mashudi; Purnama, Shilmy (Journal of Civic Education, 2025)
This article aims to analyze of the implementation of character education (PPK) at SMP Negeri 3 Sajingan Besar, Sambas Regency, a school located on the strategic Indonesia-Malaysia border. Employing a qualitative method, the research gathered data from the Principal, Deputy Principal, Civics Teacher, and students, to see the effectiveness and challenges of the program. The findings establish that PPK is systematically executed through four integrated strategies: routine activities (e.g., flag ceremonies, national songs), spontaneous actions (e.g., conflict mediation), exemplary conduct (e.g., proper language use, forming the TPPK), and conditioning (e.g., the 3S culture and kerja bakti). Implementation is strongly supported by the school's compliance with government regulations, its crucial position as the closest school to the border, and the existing ethnic and religious diversity which naturally promotes tolerance. However, significant obstacles remain, primarily the students' lack of awareness regarding the importance of national identity and the persistent issue of frequent bullying both inside and outside the school. To counter these problems, the school focuses on providing understanding and positive examples, alongside establishing active collaboration with parents. The study acknowledges its limitation to a single educational unit in Sambas, suggesting caution when generalizing the findings to other border regions.